Rhetorical Analysis of Dr. Tirta's TikTok Content on Coffee Consumption Patterns - Louise Darma Muthaharroh; Safinatun Naja; Asfarazain Salsa Bila Azzahro; Farida Nurul Rahmawati (Yayasan Citra Dharma Cindekia, 2026)
This study aims to analyze rhetorical strategies in health communication delivered through social media, particularly in Dr. Tirta’s TikTok content regarding coffee consumption patterns. The background of this study is based on the increasing use of social media as a source of health information, as well as the high level of coffee consumption among the public, which is not always accompanied by an adequate understanding of healthy consumption patterns. This research employs a descriptive qualitative approach using text discourse analysis to examine the verbal and nonverbal elements in the video entitled “How Many Times a Day Does Dr. Tirta Drink Coffee?”. The analysis is conducted using Aristotle’s rhetorical theory, which encompasses ethos, logos, and pathos. The findings indicate that Dr. Tirta utilizes ethos through his credibility as a medical professional and his authentic communication style, logos through the delivery of fact-based information and medical reasoning, and pathos through an emotional approach that resonates with the audience’s daily experiences. The combination of these three rhetorical elements results in health messages that are persuasive, easy to understand, and relevant to the audience’s context. This study confirms that rhetorical strategies play an important role in enhancing the effectiveness of health communication on social media.